A mathematical solution of the optimum takeoff angle in long jump - Tsuboi, K. (Procedia Engineering, 2010)
We successfully derive the optimum takeoff angle in long jump based on the maximization problem of the flight distance. The takeoff model proposed here includes three parameters: the horizontal speed of the centre of mass, the takeoff speed and the takeoff angle. The optimum takeoff angle is determined explicitly as a function of these parameters. The estimation of the optimum angle shows good agreement with the measured data of Mike Powell and Carl Lewis, which demonstrate the effectiveness of the present model and its solution.